Pembuatan Metil Ester dari Minyak Biji Nyamplung dengan Katalis Zeolit Alam Terembani Zirkonia: Synthesis Methyl Ester from Nyamplung Oil using Zirconia based Natural Zeolite as Solid Heterogeneous Catalyst - Adrian Ristanto Adi; Yoga Supriyanto; Hidayat, Arif (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2024)
Biodiesel is a renewable energy source that has great potential as an alternative fuel to replace fossil diesel in diesel engines. The potential of feedstock from non-edible oils for biodiesel is being considered with the aim of biodiesel production without negatively impacting food issues. Nyamplung oil is a type of non-edible oil in nature that can be used as a source for biodiesel esterification. This research aims to produce methyl ester from nyamplung oil using Zirconia-embedded natural zeolite catalyst (ZrO2/natural zeolite). The catalyst used was prepared from natural zeolite by impregnation method. The results showed that the free fatty acid conversion was obtained at 89.0% which was achieved at a temperature of 60°C in 80 minutes, a catalyst concentration of 5% wt. of the oil, and a molar ratio of methanol to oil at 9:1 for biodiesel production. The results of this study indicate that ZrO2/natural zeolite catalyst is used to produce biodiesel from nyamplung oil.